2018
DOI: 10.1111/ipd.12372
|View full text |Cite
|
Sign up to set email alerts
|

Pulp necrosis and crown discoloration: a systematic review and meta‐analysis

Abstract: The positive association between pulp necrosis and crown discoloration should be considered with caution once the diagnosis of pulp necrosis was performed by limited criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Out of the included SRs, the oldest one was published in 1999 12 and two were published between 2000 and 2010 16,17 . Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 .…”
Section: Resultsmentioning
confidence: 99%
“…Out of the included SRs, the oldest one was published in 1999 12 and two were published between 2000 and 2010 16,17 . Forty‐four SRs had been published in last six years (2015‐2020) 18‐78 . Twenty‐eight of the SRs had been published in Dental Traumatology, 16,17,20‐27,29,30,36,39‐41,44,45,59,60,67,69,71,74,75,77,78 and five were from the Cochrane database 38,46,50,53,70 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, in the clinical and radiographic follow-up of traumatized teeth of up to 12 months, it was observed that the main clinical sequelae found in primary teeth was crown discoloration (24.3%), data similar to other reports in literature [25,26], which also observed discoloration as the most frequent sequela, and often trauma is only noticed by parents due to the aesthetic change of tooth color. However, there are controversies regarding the appropriate treatment for primary teeth that have changed crown color, since the traumatized primary tooth can become rosy, yellowish or grayish [24,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Grayish discolorations are the most controversial in relation to treatment, and may be related to slight pulp changes, that is, evidence of periapical inflammation in 1 to 2 months after trauma, and coloration may disappear in a few weeks; however, if the grayish color remains, and the normality of the periodontal structures is verified, follow-up and further examinations must be performed at 6 and 12 months [24,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the reliability of the systematic review, the risk of bias of the sixteen studies was conducted using the Fowkes and Fulton 19 checklist. This quality assessment tool has been used in many recent systematic reviews 38‐40 and provides a standard summary of methodological topics considered important when assessing the risk of bias in observational studies. According to the critical analysis, four studies produced interesting results, but had problems 32,34,36,37 ; three of these 32,34,36 had no methodological soundness because they did not collect data on confounding factors and so their observed associations may have occurred by chance, and one study 37 had these flaws as well as the possibility of an erroneously association.…”
Section: Discussionmentioning
confidence: 99%